Sinergi Mahasiswa dan Masyarakat dalam Pengembangan Wisata Edukasi Bambu Kampoeng Deling di Desa Sumberdem - Aldeon Caesaro Pamungkas; Rendi Yulianto; Rajwa Aamirah Notariussy; Ivania Jaziel Christiani; Hafidl Arsy Nusa; Hadya Rhasya Putra Irawan; Filemon Iman Kasih; Cilla Nafisah Rana Kayla; Ardi Louisten Uruilal; Siti Putri Lestari (PT. Hasba Edukasi Mandiri, 2026)
The development of local village potential is often constrained by suboptimal natural resource management and community capacity, as seen in Sumberdem Village, which has a large bamboo forest area yet remains underutilized. This program aims to develop Kampoeng Deling as an educational tourism destination based on conservation and community empowerment. The methods employed include field surveys, observation, vegetation mapping, preparation of cooperation documents, development of educational facilities, and community training carried out participatively from January to February 2026. The results indicate the establishment of a tourism management foundation through a Memorandum of Understanding (MoU) between parties, identification data and bamboo distribution maps, an educational park, information boards, a profile booklet, and improved capacity of prospective tour guides. This program has contributed to increased community knowledge, conservation awareness, and local economic opportunities. Overall, the activities have successfully laid the groundwork for sustainable tourism development, although further promotion, continued assistance, and long-term evaluation are still required. Therefore, ongoing multi-stakeholder collaboration is recommended to ensure the sustainability and optimal development of Kampoeng Deling.